Regional variation in clinical-trial risks: a large-scale analysis of 585 clinical trials - de Viron, Sylviane; Young, Steve; Trotta, Laura; Buyse, Marc (BMJ open, 2025)
ObjectivesTo assess 10 common indicators of clinical trial risks across regions.DesignRetrospective pooled analysis of routine central-monitoring outputs.Data sourcesData came from a central-monitoring platform (2015–2025), which contains data from clinical trials conducted worldwide by 46 different sponsors and contract research organisations acting on behalf of sponsors. Trial sites were grouped into seven geographic regions—North America, Central/South America, Western Europe, Eastern Europe, Africa/Middle East, Asia, Pacific—to assess regional differences in monitored clinical-trial risks.Main outcome measuresPrimary outcome—Relative Key Risk Indicator (KRI) risk score, defined as the relative risk in the selected region in comparison to the expected risk computed using data across all regions globally for 10 common risks usually assessed in clinical trials.ResultsA total of 585 studies involving 56 189 sites comprising data from all regions of the world were used in the analysis. No obvious concerns were identified regarding the conduct of reliable clinical research in any region. However, for some KRIs (eg, off-schedule visit rate, protocol deviation rate and screen failure rate), there was substantial variability observed of relative risks across regions. Conversely, some other KRIs (eg, visit-to-entry cycle time and adverse event reporting rate) had a very narrow distribution across all regions.ConclusionsThese results highlight regional differences across some common risks that may help clinical trials sponsors to plan future trials and take prospective measures to reduce KRI-related risks in some regions of the world.